Employment Status Change and New-Onset Depressive Symptoms in Permanent Waged Workers - Kim, Hyung Doo (Saf Health Work, 2021)
BACKGROUND: This study aimed to investigate the relationship between changes in employment status and new-onset depressive symptoms through a one-year follow-up of permanent waged workers. METHODS: We analyzed the open-source data from the Korea Welfare Panel Study. Using the 2017 data, we selected 2,314 permanent waged workers aged 19 to 59 years without depressive symptoms as a base group. The final analysis targeted 2,073 workers who were followed up in 2018. In 2018, there were five categories of employment status for workers who were followed up: permanent, precarious, unemployed, self-employed, and economically inactive. Multiple logistic regression was used to determine the association between employment status change and new-onset depressive symptoms. RESULTS: Adjusted multiple logistic regression analysis showed that among male workers, workers who went from permanent status to being unemployed (odds ratio: 4.50, 95% confidence interval: 1.19 to 17.06) and from permanent status to being precarious workers (odds ratio: 3.15, 95% confidence interval: 1.30 to 7.65) had significantly high levels of new-onset depressive symptoms compared with those who retained their permanent employment status. There were no significant increases in new-onset depressive symptoms of male workers who went from permanent status to being self-employed or economically inactive. On the other hand, no significant differences were found among female workers. CONCLUSION: Our study suggests that the change of employment status to precarious workers or unemployment can cause new-onset depressive symptoms in male permanent waged workers.